2014
DOI: 10.1177/0268355514555546
|View full text |Cite
|
Sign up to set email alerts
|

Endovenous laser ablation in patients with wide diameter of the proximal segment of the great saphenous vein: Comparison of methods

Abstract: Our experience of using the laser 1560 nm wavelength for the treatment of the chronic venous disease in patients with wide diameter of the proximal segment of great saphenous vein shows the safety and efficacy of this technique.EVLA has to be personalized on the size of the segments of vein in patients with wide proximal segment of great saphenous vein.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

0
8
1
2

Year Published

2017
2017
2024
2024

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 13 publications
(11 citation statements)
references
References 18 publications
0
8
1
2
Order By: Relevance
“…Some research has suggested that using EVLA to treat incompetent veins with an approximate diameter measurement between or over 8 to 15 mm is unsuitable, and, in some instances, open-surgery has even been recommended as preferential. [8][9][10]12,13 In this report, 17.31% of a clinical cohort had a vein diameter measuring 15 mm or over and we did not observe any difference in the short-term surgical outcome in those with a smaller diameter. This equates to 334 veins that would have otherwise been recommended for suboptimal open surgical intervention.…”
Section: Discussioncontrasting
confidence: 42%
See 1 more Smart Citation
“…Some research has suggested that using EVLA to treat incompetent veins with an approximate diameter measurement between or over 8 to 15 mm is unsuitable, and, in some instances, open-surgery has even been recommended as preferential. [8][9][10]12,13 In this report, 17.31% of a clinical cohort had a vein diameter measuring 15 mm or over and we did not observe any difference in the short-term surgical outcome in those with a smaller diameter. This equates to 334 veins that would have otherwise been recommended for suboptimal open surgical intervention.…”
Section: Discussioncontrasting
confidence: 42%
“…Some practitioners have classified veins that are highly tortuous or with a large diameter as unsuitable for thermal ablation and, in some instances, consider open-surgery to be a superior treatment option. [8][9][10] The objective of this study was to report our experience using EVLA to treat incompetent great saphenous vein (GSV) of any diameter. In this report, we have shown the distribution of GSV diameters that have been successfully treated with EVLA by one consultant vascular surgeon over five years and six months.…”
Section: Introductionmentioning
confidence: 99%
“…The first issue concerns the role of vein size in the treatment protocol. According to the manufacturer's recommendations, in the majority of EVL devices the linear endovenous energy density (LEED) should be adjusted to the vein diameter 2 . Here, in the article, the authors did not mention that parameter at all.…”
mentioning
confidence: 99%
“…З метою виявлення можливих чинників, здатних вплинути на вірогідність рецидиву, дані пацієнтів були проаналізовані та виділені підгрупи пацієнтів з такими ускладнюючими факторами, як варикотромбофлебіт, вроджені судинні мальформації та післятромбофлебітична хвороба. Також, згідно з даними літератури [4], на результат лікування із застосуванням ЕТ методик може впливати діаметр вени [4,5,6] та її анатомічні особливості (звивистість тощо) [4,7], але отримати такі дані для групи пацієнтів, оперованих не в нашій клініці («первинних»), було неможливо через відсутність подібних даних. Серед пацієнтів, оперованих в нашій клініці («вторинних»), лише в 1 пацієнта з діаметром ВПВ 26 мм в період 18 місяців виникла сегментарна реканалізація ділянки ВПВ, яка була усунена шляхом пінної склеротерапії (ПС).…”
unclassified